filmov
tv
Prove that `(1)/((sec theta-tan theta))-(1)/(cos theta)=(1)/(costheta)-(1)/((sectheta+tantheta)).`
![preview_player](https://i.ytimg.com/vi/0shZZDVP0po/maxresdefault.jpg)
Показать описание
Prove that `(1)/((sec theta-tan theta))-(1)/(cos theta)=(1)/(costheta)-(1)/((sectheta+tantheta)).`
Prove that `(1)/((sec theta - tan theta))-(1)/(cos theta)=(1)/(cos theta)-(1)/((sec theta+ tan theta
Prove that `(1)/((sec theta-tan theta))-(1)/(cos theta)=(1)/(costheta)-(1)/((sectheta+tantheta)).`
Prove that `(1+sectheta-tantheta)/(1+sectheta+tantheta) = (1-sintheta)/(costheta)`
Prove that sec theta +tan theta-1/tan theta-sec theta+1=cos theta/1-sin theta
sintheta-costheta+1/sintheta+costheta-1=1/sec theta-tan theta
Prove trigonometric equation 1/(sec θ + tan θ) = sec θ - tan θ
Grade10 prove that 1/ sec theta - tan theta = sec theta + tan theta
Prove that 1 + sec theta - tan theta / 1 + sec theta + tan theta = 1 - sin theta/cos theta(easy way)
DAY:13-SSC REVISION CLASSES||TSRJC||POLYCET||JATADHARA EDUCATIONAL TECHNOLOGY||21.12.2024
tan theta + 1 / tan theta = sec theta . cosec theta | Trigonometry class 10 | Trigonometry proof
RD Sharma Ex 11.1 Example-7 | Prove that sin theta/(1-cos theta)+tan theta/(1+cos theta)=sec theta
Prove that:1/(sec theta - tan theta) = sec theta + tan theta. | 10 | TRIGONOMETRY | MATHS | NAVN...
Prove Trigonometric equation √((1- sin θ)/(1+sin θ)) = sec θ - tan θ
Prove that: (tan theta + sec(theta) - 1)/(tan theta - sec(theta) + 1) = (1 + sin theta)/(cos theta)
Class10||RD Sharma||Ex11.1 Qu34ii|| sintheta-cos theta+1/sin theta+cos theta-1=1/sectheta-tan Tamil
tan theta/1-cot theta + cot theta/1-tan theta= 1+ sec theta cosec theta
tan theta+sec theta-1/tan theta-sec theta+1=1+sintheta/costheta
Prove that : (sin θ - cos θ + 1)/(sin θ + cos θ - 1) = 1/(sec θ - tan θ), using the identity sec² θ...
Prove that : root 1 + sin theta / 1-sin theta = sec theta + tan theta.
Prove that : sin theta - cos theta + 1/sin theta + cos theta - 1 = 1/sec theta - tan theta.
Tan theta + Sec theta – 1 / Tan theta – Sec theta + 1 = 1+Sin theta / Cos theta @EAG
Prove that sin theta-cos theta+1/sin theta+cos theta-1 = 1/sec theta-tan theta. easy way.
tan θ/1-cot θ +cot θ/1-tan θ=1+secθ+cosecθ || Prove using trigonometric Identities || Malayalam...
root ( 1 - cos theta )/(1+cos theta) = cosec theta - cot theta | Trigonometry class 10
Комментарии